Effects of the Architectural Layout of the Sanctuary of Pachacamac (2nd–16th Century CE, Peru) on the Exposure to Rain, Wind, and Solar Radiation from the Morphometric Analysis of Digital Surface Models - Luigi Magnini; Denise Pozzi-Escot; Janet Oshiro; Rommel Angeles; Maria Ilaria Panaccione Apa; Guido Ventura (Remote Sensing, 2024)
Natural events (floods, earthquakes, landslides, etc.) may significantly damage archaeological sites, and therefore reducing their exposure to such events represents a priority for protective and conservation activities. The archaeological Sanctuary of Pachacamac (SP; 2nd–16th century CE; Peru) covers an area of 465 hectares and includes roads, enclosures, huacas with ramps, temples, and palaces located along the central coast of Peru. This area is affected by heavy rain and winds related to the El Niño–Southern Oscillation and to intense solar radiation. We use a 30 cm resolution Digital Surface Model obtained from orthophotogrammetric data and perform a morphometric analysis using geomorphological, hydrological, and climatic quantitative parameters. Our aim is to identify the zones exposed to water flow or stagnation during rainfall, as well as the exposure to winds and solar radiation. The calculated parameters are subsequently processed with an object-based image analysis approach to identify areas with higher climate exposure. We show that the SP architectural layout controls the exposure to water stagnation or flow in the form of rainfall, whereas exposure to wind and solar radiation mainly depends on the topography of an area (e.g., the presence of hills and plains). The methodological approach proposed here may be applied and extended to other archaeological sites.